Dynamics of nitrogen translocation from mature leaves to new shoots and related gene expression during spring shoots development in tea plants (Camellia sinensis L.). Issue 2 (30th January 2020) - Fan, Kai; Zhang, Qunfeng; Tang, Dandan; Shi, Yuanzhi; Ma, Lifeng; Liu, Meiya; Ruan, Jianyun
Abstract: The contribution of N remobilization is crucial for new shoots growth and quality formation during spring tea shoots development. However, the translocation mechanism of N from source leaves to sink young shoots is not well understood. In the present study, 15 N urea was applied to mature tea leaves one week before bud break to track N remobilization in a field experiment. The dynamic changes in plant 15 N abundance, contents of amino acids, and the expression levels of genes related to N metabolism and translocation were followed during the 18‐d development of new spring shoots until three expanding young leaves. The results showed that during the growth of new shoots the amount of 15 N in the shoots increased, whereas the Ndff (N derived from 15 N‐urea) in mature leaves decreased, showing that the foliar‐applied N in mature leaves was readily exported to new shoots. This process was found to be accompanied by decline of chlorophylls. In the mature leaves, expression CsATG18a and CsSAG12 involved in autophagy was dramatically induced (> 4‐fold) at approximately nine days after the bud breaking. The genes involved in the transformation of amino acids, including primarily CsGDH2, CsGDH4, CsGLT3, CsGS1;3, and CsASN2 were upregulated by > 3‐fold after bud breaking. The expression levels of CsATG8A, CsATG9, CsSAG12, CsGS1;1, CsGDH1, and CsAAP6 correlated negatively with the Ndff in mature leaves, but positively with 15 N amount and total N amount in new shoots, suggesting these genes played important roles in N export from mature leaves. In the new shoots, the expression of most genes showed two defined peaks, one on six days and one on 12 days after bud breaking. The expression of CsGS2, CsASN3, CsGLT1, and CsAAP4 positively correlated with the 15 N amount and total N amount in new shoots. These genes might be involved in the transport and re‐assimilation of N from mature leaves. The overall results demonstrated that the translocation of 15 N from mature leaves to new spring shoots was regulated by the genes involved in autophagy, protein degradation, amino acid transformation and transport.